Decay properties of high spin states in Mn - Axiotis, M.; Gadea, A.; Märginean, N.; Lenzi, S. M.; Napoli, D. R.; Ur, C. A.; Martinez-Pinedo, G.; Brandolini, F.; de Angelis, G.; Bazzacco, D.; Borcea, R.; Cameron, J. A.; et al. (HNPS Advances in Nuclear Physics, 2019)
The electromagnetic decay properties of high spin states in 52Mn have been studied through various experiments with the GASP and EUROBALL arrays plus the ISIS charged-particle detector, the Neutron-Wall and the Recoil Filter Detector. From 7-7-particles coincidence measurements, spins and parities of these states have been determined and using the Doppler-shift attenuation method the mean life of some of these states have been determined. These results are compared with large scale shell-model calculations in the full fp shell.